IMPACT OF COMMUNICATIVE COMPETENCE AMONG PEOPLE DURING SPEECH. (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2024)
This article explores the significance of communicative competence in enhancing the effectiveness of spoken interactions across various social, academic, and professional settings. It delves into how communicative skills contribute to better understanding, cooperation, and problem-solving. By examining key components of communicative competence—linguistic, sociolinguistic, discourse, and strategic skills—the article demonstrates its essential role in developing clear, impactful speech and fostering interpersonal connections. Through a review of relevant research, this study underscores the necessity of communicative competence as a fundamental element in modern social interactions.